2021
DOI: 10.1108/jrim-03-2020-0059
|View full text |Cite
|
Sign up to set email alerts
|

How to motivate opinion leaders to spread e-WoM on social media: monetary vs non-monetary incentives

Abstract: PurposeOpinion leaders are increasingly important as a source of information, with consumers judging them to be more credible than other media and more influential than other consumers. Thus, companies have an interest in engaging opinion leaders to post about products and brands, and the authors analyse different incentives for encouraging them to spread the word on social media (via electronic word-of-mouth [e-WoM]).Design/methodology/approachA 2 × 3 between-subjects experimental design was developed in whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 52 publications
(102 reference statements)
0
19
0
Order By: Relevance
“…Compared to traditional celebrity endorsements by movie or athletic stars with a higher social status, many livestream shopping anchors are ordinary people, also known as "grassroots" celebrities (Wang, 2021). They usually have a high level of product knowledge and experience (López et al, 2021) and are more close to the life of an average consumer and therefore capable of becoming more interactive with followers and potential consumers (Al-Emadi and Yahia, 2020). During social media interactions, followers also may respond to the anchors, thus establishing a social relationship between them (Delbaere et al, 2020).…”
Section: Literature Review and Hypotheses Livestream Shopping And Anchorsmentioning
confidence: 99%
“…Compared to traditional celebrity endorsements by movie or athletic stars with a higher social status, many livestream shopping anchors are ordinary people, also known as "grassroots" celebrities (Wang, 2021). They usually have a high level of product knowledge and experience (López et al, 2021) and are more close to the life of an average consumer and therefore capable of becoming more interactive with followers and potential consumers (Al-Emadi and Yahia, 2020). During social media interactions, followers also may respond to the anchors, thus establishing a social relationship between them (Delbaere et al, 2020).…”
Section: Literature Review and Hypotheses Livestream Shopping And Anchorsmentioning
confidence: 99%
“…Others have delved deeper into ways of improving the quality of eWOM and have examined the impact of incentives, product experience, emotions and interpersonal relationships on review likelihood, helpfulness and effectiveness. For instance, López et al (2021) found that opinion leaders were more likely to provide reviews if they were offered free products compared to monetary incentives. Jia et al (2021) showed that the effectiveness of length of a review depended on product type (think vs feel).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, monetary rewards can shift consumer motivation from intrinsic to extrinsic factors, such as discounts, as demonstrated by Vilnai-Yavetz and Levina (2018). Social pressure also plays a role, with financial rewards potentially reducing the intention to post reviews due to anticipated negative reactions from followers (Lopez et al , 2021).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%